CESifo World Economic Survey November 2016 - Johanna Garnitz; Gernot Nerb; Dorine Boumans; Klaus Wohlrabe; Markus Reischmann; Marina Riem; Andreas Steiner (CESifo World Economic Survey, 2016)
World Economic Climate: World Economic Climate brightens again - Economic Expectations: Economic expectations turn positive - Inflation: Inflation to remain low in most countries - Currencies: US dollar expected to rise further - Interest Rates: Interest rates expected to rise - Special Topic: Public debt management
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies